Optimizing Plantation Waste for Alternative Feed in Integrated Crop-Livestock System: A Case Study from Bulukumba, South Sulawesi - Astati, Astati (Universitas Islam Negeri Alauddin Makassar, 2026)
Bulukumba Regency holds significant potential for developing an integrated crop-livestock system through the utilization of plantation waste such as copra meal, coconut husk, cocoa pod husk, and clove leaves as alternative feed for ruminant livestock. This research employed a case study approach using qualitative methods, supported by secondary data and laboratory analysis of the nutritional content of the waste materials. The study also assessed the level of utilization by farmers and livestock keepers, as well as the challenges encountered in its application. Data were collected through in-depth interviews, field observations, and documentation. The findings revealed that the use of plantation waste as animal feed remains low due to limited technical knowledge, inadequate processing technology such as fermentation, and weak institutional support and extension services. In fact, utilizing this waste could reduce feed costs by up to 40% without compromising livestock performance. This research proposes a zero-waste-based integration model consisting of several stages: mapping the potential of local waste resources, providing technical training, establishing farmer group enterprises, and conducting continuous monitoring. Regional policies and institutional support are necessary to strengthen the implementation of this model in order to create a sustainable and environmentally friendly crop-livestock system in Bulukumba.